Pilot feasibility randomized clinical trial of negative‐pressure wound therapy versus usual care in patients with surgical wounds healing by secondary intention. Issue 3 (23rd April 2018) - Arundel, C.; Fairhurst, C.; Corbacho‐Martin, B.; Buckley, H.; Clarke, E.; Cullum, N.; Dixon, S.; Dumville, J.; Firth, A.; Henderson, E.; Lamb, K.; McGinnis, E.; et al.
Abstract : Background: Surgical wounds healing by secondary intention (SWHSI) are increasingly being treated with negative‐pressure wound therapy (NPWT) despite a lack of high‐quality research evidence regarding its clinical and cost‐effectiveness. This pilot feasibility RCT aimed to assess the methods for and feasibility of conducting a future definitive RCT of NPWT for the treatment of SWHSI. Methods: Eligible consenting adult patients receiving care at the study sites (2 acute and 1 community) and with a SWHSI appropriate for NPWT or wound dressing treatment were randomized 1 : 1 centrally to receive NPWT or usual care (no NPWT). Participants were followed up every 1–2 weeks for 3 months. Feasibility (recruitment rate, time to intervention delivery) and clinical (time to wound healing) outcomes were assessed. Results: A total of 248 participants were screened for eligibility; 40 (16·1 per cent) were randomized, 19 to NPWT and 21 to usual care. Twenty‐four of the 40 wounds were located on the foot. Participants received NPWT for a median of 18 (range 0–72) days. Two participants in the NPWT group never received the intervention and 14 received NPWT within 48 h of randomization. Five participants in the usual care group received NPWT during the study. Ten of the 40 wounds were deemed to have healed during the study. Conclusion: A full‐scale RCT to investigate the clinical and cost‐effectiveness of NPWT for SWHSI is feasible. This study identified crucial information on recruitment rates and data collection methods to consider during the design of a definitive RCT. Registration number: ISRCTN12761776 (www.iscrtn.com ) Abstract : A full‐scale RCT to investigate the clinical and cost‐effectiveness of negative‐pressure wound therapy (NPWT) for surgical wounds healing by secondary intention (SWHSI) is feasible. Crucial information on recruitment rates and data collection methods, to consider during the design of a definitive RCT, has been identified. Little evidence yet of NPWT cost‐effectiveness